Death Distress and Religiosity Among Spanish Patients Diagnosed With Depression and Anxiety - Armas Arráez, Milagros; Padilla, Gustavo M.; Fernández-Mateos, Luz M.; Sánchez-Cabaco, Antonio (OMEGA - Journal of Death and Dying, 2024)
Death is a common source of uncertainty and fear for humans. Religious beliefs are among the strategies that alleviate such discomfort. The aim of this study was to explore the correlation between Death Distress and religious practices while considering other associated variables (near-death experiences, death of loved ones, and psychiatric diagnoses). The Death Anxiety Scale, Death Depression Scale-Revised, and Death Obsession Scale were administered to 400 Spanish psychiatric outpatients. Anxiety was found to be crucial for the development of Death Distress across all associations. A relation between Death Distress and Catholicism was found, albeit significantly mediated by the frequency of practice.
Keywords: death anxiety; death distress; death obsession; fear of death; religiosity; Scopus; JCR